Pengaruh Sistem Informasi Manajemen: Kepuasan Konsumen dan Keputusan Pembelian Tiket MPL Mobile Legend di Aplikasi Blibli.com - Farhan Saputra; Franciscus Dwikotjo Sri Sumantyo (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
This study aims to determine consumer satisfaction which is influenced by the management information system and the decision to buy MPL Mobile Legend tickets is influenced by the management information system. The object of this research is consumers who buy MPL Mobile Legend tickets on the Blibli.com application. The research method used is descriptive quantitative, which uses SPSS version 27 to process the data. The population in this study is 147 people with a research sample of 50 people. The sampling technique used is accidential sampling. Tests performed in the form of t-test, f-test and test the coefficient of determination. The results of this study are: 1) Customer satisfaction is partially influenced by the management information system in the Blibli.com application; 2) The decision to purchase MPL Mobile Legend tickets is partially influenced by the information management system in the Blibli.com application; and 3) Consumer satisfaction and purchasing decisions are simultaneously influenced by the management information system in the Blibli.com application.